POSSIBILITIES FOR UTILIZATION OF WASTE WATER AND RESIDUAL WOOD FIBRES IN THE PRODUCTION OF HARDBOARDS - Savov, Viktor; Antov, Petar; Neykov, Nikolay (Innovation in Woodworking Industry and Engineering design, 2021)
Despite the continuous introduction of new materials and technologies in the production of wood-based composites, hardboards (HB), remain in the range of wood products, due to their good consumer and exploitation properties. The production of these products is characterized by the intensive consumption of raw materials. In the wet production process, much of the raw material used is taken up by water involved in the formation of the wood-fibre mat. It forms a significant share in the value of the finished product, resulting in a smaller added value. At present, the utilization of wastewater from the production of the HB is unsatisfactory. Its high fibre content creates sludges that can be recycled or thermally utilized. The present study is aimed at reviewing the possible methods of utilizing the wastewater and fibre sludge in it. This will provide the Bulgarian producers with a means of enhancing production efficiency and applying the circular economy principles.